Gemcitabine cationic polymeric nanoparticles against ovarian cancer: formulation, characterization, and targeted drug delivery - Sankha Bhattacharya; Md Meraj Anjum; Krishna Kumar Patel (Taylor & Francis Group, 2022)
This study focused on gemcitabine (GTB) delivery of cationic polymeric nanoparticles to treat ovarian cancer in order to promote effective localized delivery and drug retention during biological discharge. To begin, four GTB-loaded polymer nanoparticles were prepared: chitosan nanoparticles (CS-NPs), polysarcosin nanoparticles (PSar-NPs), poly-l-lysine & polysarcosin nanoparticles (PLL-PSar-NPs), and chitosan & polysarcosin nanoparticles (CS-PSar-NPs). Based on preliminary particle size, zeta potential, encapsulation efficiency, DSC, surface morphology, release profiling, and cellular internalization studies using rhodamine 123 and Nile red fluorescent markers, it was hypothesized that CS-PSar-NPs could be the best cationic formulation with strong biocompatibility and anticancer activity against the OVCAR-8 ovarian cancer cell line. To improve effective targeting, cellular penetration, and in vitro cytotoxicity, epidermal growth factor receptor variation III (EGFRvIII) is attached over all four polymeric nanoparticles. Confocal imaging revealed that EGFRvIII-conjugated cationic GTB polymeric nanoparticles had a greater cellular uptake and double internalization capabilities than unconjugated nanoparticles, as well as time-dependent cell entrance. GTB and EGFRvIII-conjugated polymer nanoparticles would have a stronger potential to infiltrate ovarian cancer cells during the first hour of incubation. According to TEM and FTIR findings, EGFRvIII conjugation across the non-target CS-PSar-NP surface was successful, making CS-PSar-NPS-EGFRvIII more target-specific and thus a safer drug delivery candidate for ovarian cancer treatment.HighlightsGTB loaded non-target CS-PSar-NPs & active targeted CS-PSar-NPs-EGFRvII developed.SEM, AFM, DSC, particle size, zeta potential, internalization performed for CS-PSar-NPs.MTT & CLSM study confirmed CS-PSar-NPS-EGFRvII was binding specific to OVCAR-8 cellsFabrication of EGFRvII over nanoparticles confirmed by TEM.CS-PSar-NPS-EGFRvII safer candidate for ovarian cancer.